Design and development of upscaled automated phase controlled impact device for operational modal testing / Lee Derk Huan - Lee , Derk Huan (2019)
In recent years, lab-scale Automated Phase Controlled Impact Device (APCID) for small rotating machines had been successfully developed for Impact-Synchronous Modal Analysis (ISMA). In response to this, an upscaled APCID is developed for medium sized industrial machines. The concept designs are first generated to meet the design requirements of creating a high impact force device that is supported by a safe, reliable, robust and portable base. A weighted selection matrix is used to evaluate the concepts to select the most suitable concept for design development. Solidworks is used to develop detail drawings in 2D and 3D for fabrication and computational analysis purpose. ANSYS Workbench 19.1 is used to perform static and dynamic analysis on the upscaled APCID design. The analysis showed that the selected APCID design is structurally safe and will not fail during operation as the safety factors are all more than 1. As such, a prototype weighing 32kg is fabricated and the overall dimension is 1390 x 420 x 1025 mm (L x W x H) and 700 x 420 x 820 mm (L x W x H) for fully extended and folded configurations respectively. The upscaled APCID is recalibrated using solenoid voltage level, activation time of solenoid and separation distance to ensure the device can supply high impact force to excite the industrial machines as well as generate smooth impact profiles that are similar to the lab-scale APCID. Generally, the impact force increases with increase of voltage level but increases until a limit and then decreases for increase in activation time of solenoid and separation distance. At 42V, the maximum impact force achieved is 259.702 N and 346.297 N for vertical and horizontal impacts. This is achieved using an activation time of 50ms for both cases and 7mm and 8mm separation distance for vertical and horizontal impacts respectively. In conclusion, the upscaled APCID developed is a success as it generates impact force as required to perform ISMA on industrial machines.